Conflicts between conservative Christian institutions and secular groups in sub-Saharan Africa: Ideological discourses on sexualities, reproduction and HIV/AIDS - Mantell, Joanne E.; Correale, Jacqueline; Adams-Skinner, Jessica; Stein, Zena A. (Global Public Health, 2011)
Religious and secular institutions advocate strategies that represent all points on the continuum to reduce the spread of HIV/AIDS. Drawing on an extensive literature review of studies conducted in sub-Saharan Africa, we focus on those secular institutions that support all effective methods of reducing HIV/AIDS transmission and those conservative religious institutions that support a limited set of prevention methods. We conclude by identifying topics for dialogue between these viewpoints that should facilitate cooperation by expanding the generally acceptable HIV/AIDS prevention methods, especially the use of condoms.
Free
Keywords: Christian Church; Evangelical; HIV/AIDS; Pentacostalism; Religious institutions; Roman Catholicism; condoms; gender; homosexuality; prevention; secular groups; sexual and reproductive health rights; sub-Saharan Africa